Uji Fitokimia Oryza sativa L. Wojalaka dari 4 Kabupaten di Pulau Sumba - Jennilien Merinda Ghello (Mathematics Education Study Program, 2025)
As a major cereal crop in Indonesia, rice (Oryza sativa L.) plays a crucial role in supporting the food needs of the Indonesian population. There is one unique variety that is still not widely known for its benefits, such as the rice that produces black rice, which is known to have a much higher nutritional content compared to regular white rice. In the East Nusa Tenggara region, this variety is better known as Wojalaka. Therefore, this study was conducted to analyze the active flavonoid content of black rice from four different districts on Sumba Island. Phytochemical tests were performed to determine which district's variety has the highest flavonoid content, so that it can be widely known and consumed as a healthy food option. The results showed that the Wojalaka variety with the highest flavonoid content is from East Sumba district. This is because, in terms of biophysics, the area is more supportive in increasing flavonoid content as one of the secondary metabolites.